Keterlibatan Netizen pasca Insiden dalam Olahraga: : Analisis Media Sosial pada Tragedi Kanjuruhan - Dhahir, Darman Fauzan (Jurnal Pekommas, 2023)
Abstract - The tragic football stampede in Kanjuruhan in October 2022 resulted in significant public concern and engagement, prompting a study to analyze online public sentiment and engagement in the aftermath of the event, focusing on the role of social media in shaping public perceptions and reputation of such incidents. The research employed a mixed-methods approach, including content and sentiment analysis of online news articles and social media posts. The findings contributed to the understanding of the impact of social media on public sentiment and engagement, as well as the need for further research on the effects of social media on public discourse, particularly in the context of tragic events. The study found that social media played a crucial role in shaping public perceptions, selling discussions, and elevating the popularity of such incidents. The analysis provided valuable insights into the implications of social media engagement and the need for further research to understand its broader impact and the influence of cultural and social factors on public responses to tragic events.